LITERASI EKONOMI SYARIAH TERHADAP ADAT DAGANG PELAKU EKONOMI PASAR LOS BATU KANDANGAN - Nor Alia; Muhammad Iqbal Sanjaya (Al-Ujrah | Jurnal Ekonomi Syariah, 2023)
This research is based on the diversity of ethnic groups and ethnic tribes spread throughout Indonesia, one of which is the Banjar tribe, which is an economic player in the Los Batu Kandangan market. The traditions formed are not apart from the doctrines of religious teaching that are growing in the local territory. This research aims to learn about the economic literacy of Los Batu Kandangan market economic actors and the impact of the economic literature of the Los Batu Kandangan market economic actors on the traders’ custom. This research is field research with a qualitative approach. Subjects in this study are Banjarese who became an economic actor in the Los Batu Kandangan market. The subject selection technique used in this research was purposive sampling. Data collection techniques include observations, interviews, and documentation. According to the results of the research shows that the traditions formed are a blend of local culture with the development of the literature and religious teachings of Islam existing in Hulu Sungai Selatan district and they are in wellliterate category, which has been described in some indicators of Islamic economic aspects.